PENDEKATAN TEORI KOMIK PADA ADEGAN RELIEF KRESNAYANA CANDI WISNU - yohannes sambodo (Institut Seni Indonesia Yogyakarta, 2019)
Reliefs and comic have a connection in context of research just because of the presence of panel. The Kresnayana Relief of Visnu Temple in Prambanan Yogyakarta is considerably an interesting object of reserach. The relief itself is a story of The God Visnu who reincarnates to be a human named Kresna. Because such relief has a story, the research is set forth about the identification of comic elements that contained in the reliefs using comic theories.Various comic elements could be learned as theories wrote by Scott McCloud. It is not likely all the elements could be found in it though, mainly caused by two different medium. Only couple can become essential such as panels, characters and panel transition. The other elements of comic are also useful for examining the object, except any part of words.As the results, Kresnayana reliefs and comic are indicates some similarities as well as dissimilarities in their elements. A panel is completely joint up from square stone pieces. Also, the gutter is unique, it is shown with two columns that enclose both of the panel sides. The panel transition on the Kresnayana relief is following the standard as the way of pradaksina.